2004
DOI: 10.1359/jbmr.040704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LRP5 Polymorphisms on Normal Variation in BMD

Abstract: Genetic studies based on cohorts with rare and extreme bone phenotypes have shown that the LRP5 gene is an important genetic modulator of BMD. Using family-based and case-control approaches, this study examines the role of the LRP5 gene in determining normal population variation of BMD and describes significant association and suggestive linkage between LRP5 gene polymorphisms and BMD in >900 individuals with a broad range of BMD.Introduction: Osteoporosis is a common, highly heritable condition determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 34 publications
5
94
0
3
Order By: Relevance
“…28 A third study confirmed both linkage and association of LRP5 alleles with BMD in 152 osteoporotic probands, their families and 160 women with BMD greater than 2.5 standard deviations above young normals, all recruited from a single region in England. 29 In keeping with our own findings that LRP5 SNPs #5 and #6 in exons 9 and 10 were associated with BMD in men, but not women, the latter study reported within-family association between an intronic SNP near exon 21 and BMD of the hip, which was stronger in males. Moreover, linkage analysis revealed linkage between SNP #9 and total hip and femoral neck BMD, and comparing osteoporotic probands to unrelated postmenopausal women with high BMD revealed three other SNPs in exons 8 (rs545382), 9 (rs2277268), and 21 (IVS21 +52c<a) to be associated with BMD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…28 A third study confirmed both linkage and association of LRP5 alleles with BMD in 152 osteoporotic probands, their families and 160 women with BMD greater than 2.5 standard deviations above young normals, all recruited from a single region in England. 29 In keeping with our own findings that LRP5 SNPs #5 and #6 in exons 9 and 10 were associated with BMD in men, but not women, the latter study reported within-family association between an intronic SNP near exon 21 and BMD of the hip, which was stronger in males. Moreover, linkage analysis revealed linkage between SNP #9 and total hip and femoral neck BMD, and comparing osteoporotic probands to unrelated postmenopausal women with high BMD revealed three other SNPs in exons 8 (rs545382), 9 (rs2277268), and 21 (IVS21 +52c<a) to be associated with BMD.…”
Section: Discussionsupporting
confidence: 81%
“…It is possible therefore that differences in muscle strength or physical activity between men and women could modulate the influence of LRP5 polymorphisms on bone mass that in some previous studies have demonstrated gender-specific effects. [28][29][30] There were several potential limitations to our study. First there were some inconsistencies between the significant main effects of a SNP #6 mostly on the hip in men ≤60 years and the interaction of this SNP with physical activity in all men on spine BMD.…”
Section: Discussionmentioning
confidence: 97%
“…Some found an association of hypercholesterolemia with lower BMD [5][6][7][8][9][10], and others with higher BMD [11], while yet others found no association at all [12,13]. On the other hand, both in vitro and in vivo animal model studies have demonstrated some detrimental effects of hypercholesterolemia or dyslipidemia on bone metabolism [14][15][16][17][18][19][20][21][22][23]. In in vitro studies, osteoblastic differentiation has been shown to be inhibited by atherogenic lipids [14,15].…”
mentioning
confidence: 99%
“…The mevalonate pathway has recently been proposed as essential for not only the synthesis of cholesterol but also the regulation of bone cell proliferation or apoptosis [16,17,24]. In addition, LDL receptor-related protein 5 (LRP5) has recently been identified as a critical regulator of osteoblastic proliferation [18], and a mutation in LRP5 as causing significant reduction in BMD in both humans and mice [19,20]. More recently, a mutation in LRP6, a closely related homolog of LRP5, has been shown to lead to reduced bone mass in mice [21], and to be genetically linked with early coronary disease, metabolic risk factors, and osteoporosis in humans [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation